Design handbook : a methodical framework - Zeiler, Wim, 1956- (Groningen : Noordhoff Uitgevers, 2017)
The first edition of Design Handbook explains how you can achieve a design in the best possible way, and at the same time provide an ideal solution for the designing task. Using a design method makes the design process systematic, integrated and ideal. Why Design Handbook? * Accessible and systematical approach for methodical designing; * open for an individual design approach; * instant applicable. This book offers students an excellent introduction to a methodical way of designing. You can subsequently judge for yourself which components of the methodical design process are useful to you. The design method is very accessible and can easily be applied. It hands you the possibility of a solid, systematic and intelligent working method, therefore increasing the chances of completing the design process with a proper design. The book also helps you understand the connections within and coherence between the different disciplines.